2009
DOI: 10.1289/ehp.0900911
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Arsenic Compromises the Immune Response to Influenza A Infection in Vivo

Abstract: BackgroundArsenic exposure is a significant worldwide environmental health concern. We recently reported that 5-week exposure to environmentally relevant levels (10 and 100 ppb) of As in drinking water significantly altered components of the innate immune response in mouse lung, which we hypothesize is an important contributor to the increased risk of lung disease in exposed human populations.ObjectivesWe investigated the effects of As exposure on respiratory influenza A (H1N1) virus infection, a common and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
135
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 37 publications
12
135
0
Order By: Relevance
“…Although it is not a new concept, the study of environmentally relevant doses (concentrations) has been the focus of recent attention (Bardullas et al, 2009;Kozul et al, 2009). Myers et al (2009) concluded that high dose experiments could not be used to predict low dose results.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not a new concept, the study of environmentally relevant doses (concentrations) has been the focus of recent attention (Bardullas et al, 2009;Kozul et al, 2009). Myers et al (2009) concluded that high dose experiments could not be used to predict low dose results.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a strong dose-response relationship between As in tubewell water and skin lesion development, a precursor of skin cancer, has been observed, with even low exposure to As was shown to be problematic (Ahsan et al, 2006). Low level As intake may also play a role in diabetes prevalence, based on findings from a crosssectional study of 788 adults in the USA (Navas-Acien et al, 2008), in addition to impairing H1N1 infection immune system in responses (Kozul et al, 2009). These research findings amongst others have prompted critical re-evaluation of exposure thresholds for As (WHO/ FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1 Arsenic exposure has also been associated with altered gene expression in lung tissue from mice, including reduced expression of genes involved in innate immune responses. 2 But it's still unclear how arsenic might modify acute inflammatory responses during early-life infections and the subsequent effects on lung structure and function.…”
mentioning
confidence: 99%
“…However, the EPA standard does not cover private wells; by one estimate, as many as 25 million people in the United States who obtain their drinking water from private wells may be exposed to arsenic levels above the EPA standard. 1 Stanton suggests repeating the mouse experiments with 10 ppb inorganic arsenic to see if the influenza response still worsens. Given current guidance on arsenic in drinking water and apple juice, "We'd want to know that," says Stanton.…”
mentioning
confidence: 99%